World Health Organization success in rehabilitation 2030 including refugees’ rehabilitation across South Asia: a narrative review - Mumtaz, Nazia; Saqulain, Ghulam (Journal of the Pakistan Medical Association, 2023)
Despite acknowledging the inadequacy of rehabilitation systems to meet the ever-increasing burden of disability, the World Health Organization’s Rehabilitation 2030 initiative has not highlighted nor adequately analysed the deficiencies of the rehabilitation care structures of populous countries in South Asia. The pragmatic and operational realisation of the initiative is not high in terms of visibility in developing countries with fragmented rehabilitative care structures. Hence, the current narrative review was planned to highlight the spectrum of rehabilitation healthcare in the perspective of Sustainable Development Goal-3 with reference to the most populous South Asian countries, including Pakistan. A total of 40 relevant English-language, articles, publications, reports and online resources were reviewed. The narrative review is significant since it may result in mainstreaming the individuals with disabilities, improving their quality of life, enhance their productivity and lessen the burden and socio-economic costs of disability on the community. ---Continue